ANALISIS SWOT TERHADAP PELAYANAN HAJI DAN UMRAH PADA KBIHU AL IHSAN KECAMATAN CARINGIN KABUPATEN SUKABUMI - Eki Agustin; Farid Abdul Malik (Jurnal Ekonomi dan Bisnis, 2024)
SWOT analysis is a strategic planning method used to assess Strengths, Weaknesses, Opportunities (opportunities) and Threats (threats or challenges) in a project or business speculation. Basically, this problem arises because of a lack of analysis regarding registration, guidance, transportation, accommodation and consumption issues carried out by the party in charge, namely KBIHU itself. Because in the implementation of the Hajj pilgrimage, weaknesses are still found every year, such as the problems mentioned above, researchers need to analyze to evaluate the Hajj and Umrah services using SWOT analysis, because SWOT analysis can analyze the extent to which the development of the institution can take advantage of opportunities to suppress weaknesses, minimize all weaknesses. to face existing and future threats. This research aims to determine the SWOT Analysis of Hajj Services at KBIHU Al-Ihsan, Caringin District, Sukabumi Regency. This research uses a qualitative descriptive method. The data collection techniques used were observation, interviews, documentation, and triangulation/combination. KBIHU Al Ihsan itself is currently in strong condition and has the opportunity to achieve maximum progress, and continues to strive to provide comfortable and safe services for its congregation. KBIHU Al Ihsan services are divided into two factors, namely internal and external. The strength of KBIHU Al Ihsan itself is the availability of places to practice manasik guidance. Meanwhile, the weakness is the lack of infrastructure for the Hajj rituals. Then we looked at the opportunity for innovation from the chairman of KBIHU, namely wanting to create a miniature Hajj pilgrimage like the one in the Holy Land. The obstacle is the application of the age limit, because in the KBIHU area the majority of Hajj registrants are over 50 years old.